Laparoscopic treatment of median arcuate ligament syndrome: A rare cause of chronic severe abdominal pain - Emre Divarci; Ulgen Celtik; Zafer Dokumcu; Ahmet Celik; Orkan Ergun (Wolters Kluwer Medknow Publications, 2017)
Median arcuate ligament syndrome is a rare disorder characterized by chronic postprandial abdominal pain and weight loss caused by compression on celiac artery. A 17-year-old girl with chronic severe abdominal pain and weight loss was referred to our clinic. Other causes of chronic abdominal pain were investigated and excluded. The compression on celiac artery was detected on Doppler ultrasound and diagnosis was confirmed by computed tomography angiography. The patient underwent laparoscopic release of median arcuate ligament. There were no intraoperative complications; however, partial pain response was observed postoperatively that necessitated para-spinal ganglion blockage. The patient is symptom-free in 1-year follow-up period.